PATRZEĆ UKRADKIEM – CZYLI O PODGLĄDANIU W JĘZYKOWYM OBRAZIE ŚWIATA POLAKÓW I ROSJAN - Słupianek-Tajnert, Daria (Acta Neophilologica, 2013)
The aim of the article is to carry out an analysis of the function of the verbs podglądać/ подглядывать in the linguistic picture of world of the Russians and Poles. The anthropologically- cultural aspect used as a methodological basis for the article enabled to investigate a tremendous potential of the above-mentioned verbs to express the evaluative, associative and cultural content.